Vessel Density in Glaucoma of Different Entities as Measured with Optical Coherence Tomography Angiography - Lommatzsch, C (Clin Ophthalmol, 2019)
PURPOSE: To compare papillary and macular vessel density (VD), as measured by optical coherence tomography angiography (OCTA), in eyes with primary open-angle glaucoma (POAG), normal-tension glaucoma (NTG) and exfoliation glaucoma (XFG). METHODS: The papillary and macular VD of 40 eyes with POAG, 19 with NTG and 21 with XFG were examined using OCTA (AngioVue™). The VD was measured at two different layers of segmentation (optic nerve head: radial peripapillary capillary [RPC] and nerve head [NH]; macula: superficial [SL] and deep [DL] retinal vascular plexus) with a 4.5×4.5mm papillary and 6×6-mm macular scan. VD was calculated by an automated density measuring tool in the AngioVue™ software. RESULTS: There were no significant differences in the total value of the papillary, peripapillary and macular VD. A significantly higher VD could be measured for NTG compared to POAG, as well as for XFG in the inferior nasal peripapillary sector at RPC-segmentation and at the NH-level between NDG and XFG. CONCLUSION: OCTA can detect a difference in VD in the nasal inferior peripapillary sector in NTG compared with POAG and XFG. These findings may help to improve the understanding of further pathophysiological mechanisms.